Hematological Changes Following Low Dose Radiation Therapy and Comparison to Current Standard of Care Cancer Treatments - Alexandra Jameus; Allison E. Kennedy; Christopher Thome (SAGE Publishing, 2021)
Cancer is the second leading cause of mortality worldwide accounting for almost 10 million deaths in 2020. Current standard of care treatment varies depending on the type and stage of disease, but commonly includes surgery, chemotherapy, and/or radiation therapy. There is evidence that whole- and half-body exposure to low dose ionizing radiation can also be an effective therapeutic due to its stimulation of anti-cancer immunity. One of the limiting factors for past clinical trials using low dose radiation therapy has been adverse hematological events. However, similar hematological changes are also frequently reported following standard of care treatments in oncology. This review summarizes the effects of various cancer therapies on hematologic toxicity through the evaluation of complete blood count reports. The reviewed literature elucidates hematological trends in patients undergoing chemotherapy, and both high and low dose radiation therapy. In general, high dose radiation and chemotherapy can result in widespread changes in blood counts, with the most severe effects related to leukopenia. Overall, compared to standard of care treatments, low dose radiation results in similar, yet more mild hematological changes. Taken together, hematological toxicities should not be a limiting factor in the applicability of low dose radiation as a cancer therapeutic.